A methodology for the security evaluation within third-party Android Marketplaces. (December 2017) - Buchanan, William J.; Chiale, Simone; Macfarlane, Richard
Abstract: This paper aims to evaluate possible threats with unofficial Android marketplaces, and geo-localize the malware distribution over three main regions: China; Europe; and Russia. It provides a comprehensive review of existing academic literature about security in Android focusing especially on malware detection systems and existing malware databases. Through the implementation of a methodology for identification of malicious applications it has been collected data revealing a 5% of them as malicious in an overall analysis. Furthermore, the analysis shown that Russia and Europe have a preponderance of generic detections and adware, while China is found to be targeted mainly by riskware and malware.